1990
DOI: 10.1254/jjp.53.275
|View full text |Cite
|
Sign up to set email alerts
|

Effects of KB-5492, 1-(3,4,5-Trimethoxybenzyl)-4-((4-Methoxyphenyl)oxycarbonylmethyl)piperazine Monofumarate Monohydrate, on Gastric Lesions and Gastric Secretion in Rats

Abstract: Abstract-Effects of a newly synthesized compound, KB-5492, on gastric lesions and gastric secretion were studied in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
8
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
(3 reference statements)
1
8
0
Order By: Relevance
“…1). Shimohara et al have already reported that KB-5492 inhibits various ex perimental gastric mucosal lesions more potently than sofalcone (6). In addition, they speculated that the anti-ulcer activity of KB 5492 was mediated by enhancing mucosal de fensive factors, since KB-5492 did not affect either basal or histamine-stimulated gastric acid secretion.…”
mentioning
confidence: 98%
“…1). Shimohara et al have already reported that KB-5492 inhibits various ex perimental gastric mucosal lesions more potently than sofalcone (6). In addition, they speculated that the anti-ulcer activity of KB 5492 was mediated by enhancing mucosal de fensive factors, since KB-5492 did not affect either basal or histamine-stimulated gastric acid secretion.…”
mentioning
confidence: 98%
“…Although KB-5492 at anti-ulcer doses did not affect either basal or histamine-stimulated gastric acid secretion in rats (3,4), it increased the gastric mucosal blood flow (4) and prevented the reduction of hexosamine content induced by aspirin in rat gatric mu cosa (4). These findings strongly suggest that KB-5492 en hances gastric mucosal defensive factors.…”
mentioning
confidence: 89%
“…KB-5492, 4-methoxyphenyl 4-(3,4,5-trimethoxybenz yl)-1-piperazineacetate monofumarate monohydrate, is a new anti-ulcer agent previously shown to prevent various experimental gastric mucosal lesions in rats including those induced by oral administration of aspirin or acidified aspirin (3,4). Although KB-5492 at anti-ulcer doses did not affect either basal or histamine-stimulated gastric acid secretion in rats (3,4), it increased the gastric mucosal blood flow (4) and prevented the reduction of hexosamine content induced by aspirin in rat gatric mu cosa (4).…”
mentioning
confidence: 99%
“…KB-5492, 4-methoxyphenyl 4-(3,4,5-trimethoxybenzyl) 1-piperazineacetate monofumarate monohydrate, is a new anti-ulcer agent previously shown to prevent various experimental gastric mucosal lesions in rats (1,2). Although KB-5492, at anti-ulcer doses, did not affect either basal or histamine-stimulated gastric acid secretion (1,2), it increased gastric mucosal blood flow (2), prevent ed aspirin-induced reduction of gastric mucus (2) and pro tected the gastric mucosal barrier (3).…”
mentioning
confidence: 99%
“…Although KB-5492, at anti-ulcer doses, did not affect either basal or histamine-stimulated gastric acid secretion (1,2), it increased gastric mucosal blood flow (2), prevent ed aspirin-induced reduction of gastric mucus (2) and pro tected the gastric mucosal barrier (3). Therefore, KB-5492 has been considered to enhance gastric mucosal defensive factors.…”
mentioning
confidence: 99%